Adult acute lymphoblastic leukemia in a resource-constrained setting: outcomes after expansion of genetic evaluation - Wellington F. Silva; Mariane T. Amano; Luiza L. Perruso; Maria Gabriella Cordeiro; Renata Kiyomi Kishimoto; Aline de Medeiros Leal; Luciana Nardinelli; Israel Bendit; Elvira DRP Velloso; Eduardo M. Rego; Vanderson Rocha (Hematology, 2022)
Acute lymphoblastic leukemia (ALL) is a challenging disease with a growing genetic landscape, even though there is substantial gap between developed and non-developed countries when it comes to availability of such new technologies. This manuscript reports a 5-year retrospective cohort of newly diagnosed ALL patients and their genetic findings and outcomes. An expanded genetic evaluation by using FISH and RT–PCR was implemented, aiming to identify Ph-like alterations. Patients were treated according to our local protocol, which allocated patients according to age and Philadelphia-chromosome status. A total of 104 patients was included, with median age of 37.5 years. Philadelphia chromosome was detected in 33 cases of B-lineage. Among 45 Ph-negative B-lineage, after excluding KMT2A or TCF3-PBX1 cases, we identified 9 cases with Ph-like fusion. Ph-positive and Ph-like patients had higher initial WBC (p = 0.06). Out of 104 cases, two cases did not start chemotherapy and an early death rate of 10.8% was found. Allogeneic transplantation was performed in 18 cases, being ten performed in first CR. Three-year overall survival (OS) and 3-year event-free survival were 42.8% and 30.8%, respectively. For patients treated with a pediatric regimen, 3-year OS was 52.5%. Extramedullary disease (HR 0.42) and platelet counts (HR 0.9) were independently associated with OS. We still face excessive non-relapse mortality that compromises our results. Alternative strategies implementing FISH and RT–PCR are feasible and able to identify Ph-like fusions. Delays in allogeneic transplantation, as well as the unavailability of new agents, impact long-term survival. Measures to decrease early infection are desirable.